Prevalence of Psychological Problems Among Adolescent Students of Selected Private School at Itahari Sub-Metropolis of Eastern Nepal - Guragain, Parth; Rimal, Hem Sagar; Kafle, Tara (Journal of College of Medical Sciences-Nepal, 2019)
Background: Adolescence is the second decade of life, the crucial period demanding significant adjustment in physical, psychological and social dimensions. The main aim of this study was to access the psychological problems of adolescents in Itahari sub-metropolis. Methods: A cross-sectional study design and consecutive sampling technique was adopted for the study. The study was conducted in selected schools of Itahari Metropolitan city. From the selected schools, students of class 7 to 12 with the age range of 11-19 years were included in the study. Sample size was calculated considering the prevalence of Psychosocial Problem of similar setting. The instrument for data collection was self-administered pediatric checklist for youth, an internationally valid tool, which was divided in three parts. Part I related to socio-demographic information, part II consisted of questions regarding family and school related factors and part III was the standard tool to measure psychosocial problem. Results: The prevalence of psychological morbidity on the basis of total difficulties score was found to be 23.9% (11) in male whereas 31.5% (17) was abnormal in female. Among males, 76.1% (35) was found to have normal scores as compared to 68.5% (37) in females although the difference was found to have no statistical significance. Conclusions: The adolescent age groups have to face various psychological problems and are likely to be very common. School mental health and social services have the potential to affect the prevalence of these and other psychological disorders by assisting in the assessment, referrals and management of the affected students.